2015
DOI: 10.15252/embj.201490706
|View full text |Cite
|
Sign up to set email alerts
|

Sox2, Tlx, Gli3, and Her9 converge on Rx2 to define retinal stem cells in vivo

Abstract: Transcriptional networks defining stemness in adult neural stem cells (NSCs) are largely unknown. We used the proximal cis-regulatory element (pCRE) of the retina-specific homeobox gene 2 (rx2) to address such a network. Lineage analysis in the fish retina identified rx2 as marker for multipotent NSCs. rx2-positive cells located in the peripheral ciliary marginal zone behave as stem cells for the neuroretina, or the retinal pigmented epithelium. We identified upstream regulators of rx2 interrogating the rx2 pC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(124 citation statements)
references
References 54 publications
(81 reference statements)
5
119
0
Order By: Relevance
“…We cloned Dam-f-GFP using promoters that included ubiquitin (Mosimann et al, 2011), heat shock (Blechinger et al, 2002) and Rx2 (Reinhardt et al, 2015) in plasmids carrying transgenesis markers such as Cmlc2:GFP or RFP. Surprisingly, none of the Dam-f-GFP constructs showed GFP expression, whereas the unfused GFP construct did (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We cloned Dam-f-GFP using promoters that included ubiquitin (Mosimann et al, 2011), heat shock (Blechinger et al, 2002) and Rx2 (Reinhardt et al, 2015) in plasmids carrying transgenesis markers such as Cmlc2:GFP or RFP. Surprisingly, none of the Dam-f-GFP constructs showed GFP expression, whereas the unfused GFP construct did (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although Rx2 was provided as mRNA and was therefore expressed in the whole embryo, a careful inspection of the regions of Rx2 enrichment revealed many players known to be involved in retinal development, including Six3 (Loosli et al, 1998), Otx2 (Zuber et al, 2003), Pax6 (Loosli et al, 1998) and Sox2 (Reinhardt et al, 2015). Interestingly, we also found enrichment of Rx2 on its own proximal upstream locus (…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Müller glia cells can function as late-stage retinal progenitors of the photoreceptor lineage, with their cell bodies occasionally migrating to the horizontal cell layer to divide asymmetrically, generating one photoreceptor and one Müller glial cell [12]. To assess the existence of such Müller glial cell divisions, we carried out immunolabelling with Rx2, which allows labelling cell bodies of photoreceptor as well as Müller glial precursors of the INL (Fig 2F and 2G [30]). Some Rx2 immunoreactive cells could be indeed observed with their cell bodies located sub-apically, between the outer limiting membrane and the horizontal cell layer.…”
Section: Resultsmentioning
confidence: 99%
“…In a cancer cell line, MID1 marks Fu by ubiquitination for subsequent cleavage leading to the cytosolic retention of GLI3 (31) and thus blocks Hh signaling. In the eye, gli3 was shown to interact with other transcription factors to define retinal stem cells and gli3 may cooperate with pax6 during eye morphogenesis (42,43). Thus, a feedback loop may exist, which regulates a balance between mid1 expression with medium levels of Shh that induce mid1 and lower levels that suppress mid1 expression.…”
Section: Discussionmentioning
confidence: 99%